Reducing Plagiarism of Students’ Analytical Exposition Writing Through QuillBot Application - Komang Indra Prameswari; Myartawan, I Putu Ngurah Wage; Dambayana S, Putu Eka (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This classroom action research aimed to reduce plagiarism in students’ analytical exposition writing through the use of the QuillBot application as a supportive tool in the writing revision process. The study involved 35 students of class XI-I at SMAN 3 Singaraja. Based on the preliminary observation, most students obtained similarity percentages above the acceptable threshold after their writing was checked using Turnitin, indicating that students still experienced difficulties in paraphrasing and tended to copy information directly from internet sources. The data were collected through students’ writing drafts, Turnitin similarity reports, classroom observation, and informal interviews with the English teacher. The research was conducted in one cycle consisting of planning, action, observation, and reflection stages. The findings showed that after the implementation of the QuillBot-based instructional intervention, all students were able to reduce their similarity percentages below the acceptable threshold, indicating that both the individual and classical passing grade criteria had been achieved. Furthermore, the independent writing results showed that students were able to maintain low similarity percentages while using QuillBot independently. These findings indicate that the guided use of QuillBot in writing instruction can help reduce plagiarism and increase students’ awareness of responsible academic writing practices.